Challenges with the Concept of “Evil” - Yan, Anderson (Vox Scripturae - Revista Teológica Internacional, 2018)
Evil is an elusive concept, which attracts diverse negative experiences that need to be distinguished due to their different causes. Yet “the problem of evil” seems a challenge for theistic perspectives only if the term is taken in its literal original sense. The fact that there is a certain resistance in adopting the term “evil” to address certain unaccepted behaviours should not exclude its powerful rhetoric in the constructions of worldviews.
Keywords: Evil; Theodicy; Suffering; The problem of evil